Participação social no campo da cultura e disputas simbólicas nas políticas culturais para o circo em Fortaleza (CE) - Jocastra Holanda Bezerra; José Márcio Barros (Ciências Sociais Unisinos, 2016)
The article seeks to understand the dynamics of social participation in the field of culture. It seeks to reflect about the plurality of identities and self-representations present in the circus segment, realizing how these are articulated, integrated or do not connect with each other in the sphere of participation in the cultural policies of the city of Fortaleza, Ceará. To reflect on these questions, we analyzed the discourses and the participation of agents of the circus sector on two occasions: in the construction of the proposal of the Municipal School of Circus and the formulation of the Sectorial Circus Plan in the city.